O poder com características chinesas: o Comprehensive National Power (CNP) da China na era Hu Jintao - Silva Júnior, Valter Angelo da (2017)
This thesis addresses the topic of geopolitical power calculations from the Chinese perspective. A unique aspect of China's assessment of this subject is the use of an analytical tool called "Comprehensive National Power" (CNP) which aims to measure the power of countries and to rank them according to the results found. This Chinese method evaluation, in most of its variations, emphasizes political power as the basis of state power, as well as considering that these units are responsible for the configuration and definition of the International System, not the opposite the other way around. By doing so, it visualizes international relations from a different parameter of Western mainstream approaches, which are mostly based on material power and the power of structure constraint. This dissertation deals with this matter by contextualizing the reader from the initial theoretical foundations on state power and power in the Chinese context, in the presentation of the various CNP versions in China, and, finally, using the analysis method of Yan Xuetong (2008;2011) to evaluate the evolution of China's CNP in the Hu Jintao period (2003-2013). In this way, the thesis presents the relations between China's action - in the established time interval - and the CNP, aiming to identify how the country uses this in the assessment of the International System.